Pastoral Theology: A Methodological Approach to Analyzing Social Cases - Sonny Eli Zaluchu; Frederik Reforivan Baziduhu Zaluchu (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Religious life cannot be separated from society. As a religious institution, the church must impact society through concrete action. One of these approaches is through pastoral theology. This research aims to provide a methodological template for academics and churches, in particular, to use pastoral theology to analyze societal problems. This is necessary because some churches are still bound by dogmas that restrict the church’s role to “spiritual” matters rather than matters of concrete social concern. So, churches often distance themselves from the social theory approach in dissecting society's problems. The analytical tool used in this paper is the pastoral cycle method. A pastoral theological approach focuses on cases that have occurred or are currently occurring in society. This paper uses the case of food scarcity, namely cooking oil, which has occurred in Indonesia. The research results show that the social theological approach, which has been shunned by evangelical theology, can be used in dissecting and mapping social cases in society to contribute to the church in determining anticipatory steps and responding with concern to these social problems. Through this research, it can be concluded that the social function of the church as light and salt of the world can be achieved by using pastoral theology. The implications of this research will encourage churches to position themselves as government partners in realizing the achievement of SDG targets on the one hand and the other hand, provide new insight that pastoral theology does not only deal with “spiritual” (i.e., intangible) matters. It can be seen that a Biblical approach can be intertwined with social analysis for the purpose of social welfare.